2013
DOI: 10.1101/gad.211326.112
|View full text |Cite
|
Sign up to set email alerts
|

The retinoblastoma protein induces apoptosis directly at the mitochondria

Abstract: The retinoblastoma protein gene RB-1 is mutated in one-third of human tumors. Its protein product, pRB (retinoblastoma protein), functions as a transcriptional coregulator in many fundamental cellular processes. Here, we report a nonnuclear role for pRB in apoptosis induction via pRB's direct participation in mitochondrial apoptosis. We uncovered this activity by finding that pRB potentiated TNFa-induced apoptosis even when translation was blocked. This proapoptotic function was highly BAX-dependent, suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
94
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 57 publications
2
94
0
Order By: Relevance
“…Indeed, in some assay systems, pRB-mediated cell cycle exit correlates better with its effects on p27 levels than with changes in proteins expressed from E2F-regulated genes (Ji et al 2004). A pool of pRB has been detected at mitochondria, where it suppresses apoptosis (Ferecatu et al 2009;Hilgendorf et al 2013), providing further support for the view that pRB has effects on cell proliferation that extend beyond transcription.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Indeed, in some assay systems, pRB-mediated cell cycle exit correlates better with its effects on p27 levels than with changes in proteins expressed from E2F-regulated genes (Ji et al 2004). A pool of pRB has been detected at mitochondria, where it suppresses apoptosis (Ferecatu et al 2009;Hilgendorf et al 2013), providing further support for the view that pRB has effects on cell proliferation that extend beyond transcription.…”
mentioning
confidence: 61%
“…Other studies have shown that a subpopulation of pRB is located at the outer mitochondrial membrane, where it physically interacts with Bax and promotes apoptosis (Hilgendorf et al 2013), suggesting that pRB loss impacts multiple aspects of mitochondrial function. This observation adds to a large number of studies showing that, under specific conditions, pRB can cooperate with other factors to promote the transcriptional activation of differentiation programs and regulate the expression of apoptotic regulators (for examples, see Thomas et al 2001;Ianari et al 2009;Calo et al 2010; for review, see Attardi and Sage 2013).…”
Section: The Cellular Consequences Of Rb Inactivationmentioning
confidence: 99%
“…Besides being major controllers of the cell cycle, p16 INK4a and RB possess multiple antitumor functions [44] and their activity in regulating cell death has been shown. Over-expression of p16 INK4a has been associated with apoptosis of various transformed cells with down-regulation of the anti-apoptotic bcl-2 protein [45][46][47], and involvement of activated RB in apoptosis has been reported [48,49]. Early epigenetic changes during carcinogenesis can be induced, but also reverted, by external effectors, including food components.…”
Section: Ind Influences Cell Cycle Progressionmentioning
confidence: 99%
“…The main driver of cellular transformation in the absence of RB is thought to be unchecked cell proliferation. RB loss may also promote tumor development through inhibition of differentiation or impaired apoptosis (Ianari et al 2009;Dick and Rubin 2013;Flowers et al 2013;Hilgendorf et al 2013). In addition, RB has transcription-independent functions on chromosome condensation and maintenance of telomeric heterochromatin (Gonzalo et al 2005;Coschi et al 2010;Manning et al 2010).…”
mentioning
confidence: 99%